Peran Malaikat dalam Mimpi Yusuf Berdasarkan Matius 2:13-23: Pendekatan Genre Apokaliptik - Hauw, Siang Suk (IAKN Ambon, 2023)
This article is aimed to make the readers capable of understanding narrated story in the text of Matthew 2:13-23 from viewpoint of apocalyptic genre. Qualitative method with descriptive approach and literature study are used in analysing the text. The similar survey that discussed apocalyptic genre has been done by Kristian Bendoraitis in his article thoroughly. Bendoraitis in his article commented the meaning of apocalyptic in Matthew, the role of angel in Jesus and His disciples’ life and the role of Son of God in the time of judgement. The other scholar was David H. Wenkel. Wenkel analysed text of Mat 1-2 from apocalyptic genre side which focused on Jesus’s identity from David genealogy and the King of Israel. Here, the writer wants to show the apocalyptic elements that occupy dominantly in Joseph dream and the role of the angel in God’s salvation work. The question is whether Joseph’s dream in Mat 2:13-23 has apocalyptic aspects? The study shows that through dream, the angel of God guided Joseph in saving Jesus. Dream and angel are apocalyptic elements.AbstrakArtikel ini bertujuan untuk menghantar pembaca memahami narasi teks Matius 2:13-23 dari sudut pandang genre apokaliptik. Penelitian kualitatif dengan pendekatan deskriptif dan studi literatur digunakan dalam menganalisis teks. Penelitian atas Injil Matius yang membahas genre apokaliptik telah dilakukan oleh Kristian Bendoraitis secara cukup mendetil. Bendoraitis dalam artikelnya mengulas pengertian apokaliptik dalam Injil Matius, peran malaikat dalam kehidupan Yesus dan murid-murid-Nya dan peran Anak Manusia pada waktu penghakiman. Peneliti lainnya adalah David H. Wenkel. Wenkel menelaah teks Mat 1-2 dari sisi genre apokaliptik yang berfokuskan pada identitas Yesus sebagai keturunan Daud dan raja Israel. Sementara itu, penulis bermaksud menunjukkan unsur-unsur apokaliptik yang hadir secara cukup dominan dalam mimpi Yusuf serta peran malaikat dalam karya keselamatan Allah. Pertanyaan yang penulis ajukan adalah apakah kisah mimpi Yusuf dalam teks Mat 2:13-23 ini memiliki unsur apokaliptik? Penelitian menunjukkan bahwa melalui mimpi, malaikat Tuhan menuntun Yusuf dalam menyelamatkan Yesus yang mana keduanya adalah elemen apokaliptik.